An unfolding story: Small molecules remedy misfolded monoamine transporters. (November 2017) - Kasture, Ameya; Stockner, Thomas; Freissmuth, Michael; Sucic, Sonja
Highlights: Monoamine transporters undergo stringent quality control prior to exiting the ER. Point mutations in the monoamine transporters impair protein folding. Misfolded transporters can be rescued by either stabilizing the structure or by relaxing the stringent quality control mechanisms in the ER. Abstract: The key role of monoamine transporters is to take up neurotransmitters from the synaptic cleft and rapidly terminate neurotransmission. Monoamine transporters begin their journey by folding in the endoplasmic reticulum. Upon achieving their natively-folded state, the oligomerized transporters engage the coat protein complex II machinery and exit the endoplasmic reticulum compartment in a concentrative fashion. The transporters are subsequently sorted in the endoplasmic reticulum-Golgi intermediate complex and the Golgi apparatus, prior to reaching their pivotal site of action at the plasma membrane. Stringent quality-control mechanisms ensure that only the correctly-folded protein cargo departs the endoplasmic reticulum. Genetic point mutations in the coding sequences of monoamine transporters can trigger severe physiologic deficiencies by inducing folding defects. Protein misfolding precludes the delivery of functional monoamine transporters to the cell surface. Chemical- and/or pharmacological-chaperone molecules, which facilitate folding, have proven effective in restoring the activity of several misfolded pathological variants of monoamine transporters.